A study of motorcycle riders related to speeding behavior in Thailand’s Industrial zones - Manlika Seefong; Panuwat Wisutwattanasak; Chamroeun Se; Kestsirin Theerathitichaipa; Sajjakaj Jomnonkwao; Thanapong Champahom; Vatanavongs Ratanavaraha; Rattanaporn Kasemsri (Scientific Reports)
Abstract Despite the considerable efforts to address traffic crashes, overspeeding in industrial zones remains a primary cause in Thailand. In order to effectively against this challenge (overspeeding), the deep-rooted factors influencing speeding behaviors, particularly drivers’ risky behaviors, must be understood. Thus, this study employs the theory of planned behavior (TPB) and the framework comprising three basic Es (Education, Engineering, and Enforcement) and additional Es (Emergency response), i.e., the 3Es + Es framework, to examine these deep-rooted factors while considering the riders’ sociodemographic data. Additionally, we performed structural equation modeling to investigate the factors influencing speeding behaviors, with key findings revealing that Engineering factors significantly account for overspeeding. Conversely, we revealed that attitude, subjective norm, and perceived behavioral control (which are essential TPB components) significantly influence riders’ intentions to exhibit safe behavior, resulting in reduced speeding. Additionally, our examination of latent factors based on riders’ sociodemographic data revealed that age, marital status, income, riding experience, crash history, and traffic tickets are significant factors that determine speeding habits. Specifically, we observed that single riders and those with less than five years of riding experience were less likely to exhibit safe riding behaviors. Overall, our findings would benefit Thailand’s road-safety authorities, as we specifically proposed appropriate policies and empirical guidelines for Thailand’s industrial zones, which are prone to high crash rates. This could effectively reduce speeding among motorcycle riders and mitigate traffic crashes.